A Novel Smart Ambulance System—Algorithm Design, Modeling, and Performance Analysis - Mohammad A. R. Abdeen; Mohamed Hossam Ahmed; Hafez Seliem; Tarek Rahil Sheltami; Turki M. Alghamdi; Mustafa El-Nainay (IEEE Access, 2022)
Smart ambulance is a novel system where modern communication, computation, and sensing technologies are employed to revolutionize ambulance and emergency systems. We propose a smart system that aims to minimize the ambulance response time, travel time from patient’s location to the hospital, and the waiting time at the hospital. We utilize the road traffic conditions and hospital loading information (collected in real-time basis) to make optimal decisions (which hospital responds to the patient’s request and which ambulance it sends, which route the ambulance takes to reach the patient, which hospital the ambulance heads to after picking up the patient, and which route it should take to the selected hospital). The first two decisions are used to minimize the response time while the last two decisions are employed to minimize the door-to-needle time. We analyze the performance of the proposed algorithm; both analytically and by simulation for verification. The results showed very good consistency between simulation results and analytical results, which confirms the correctness and accuracy of the analysis. In addition, we compare the performance of our proposed smart algorithm with a previous algorithm that is reported in the literature and that minimizes the drop-off delay. The results confirmed the superiority of our smart algorithm under considered operating conditions and scenarios.